Unveiling synergies: an analysis of inter-organizational relationships in the Brazilian photovoltaic distributed generation value chain - Taís Bisognin Garlet; Fernando de Souza Savian; José Luis Duarte Ribeiro (Sustainable Futures)
Photovoltaic generation is essential to face global energy challenges and promote a transition to a sustainable future. However, as technological transformations and economic progress occur, rivalry in the photovoltaic industry intensifies. Given the different competition scenarios observed throughout the photovoltaic value chain, a deeper analysis of inter-organizational relationships is necessary to develop market strategies to increase the number of decentralized photovoltaic systems. Therefore, this article explores the dynamics of inter-organizational relationships in the Brazilian photovoltaic value chain and how they can impact the development and competitiveness of the sector. Based on literature analysis and expert interviews, drivers and barriers to establishing collaborative and synergistic relationships to expand the photovoltaic market are discussed. The results highlight the complexity of inter-organizational relationships, which manifest themselves especially as strategic partnerships, technical relationships, and commercial relationships. Relationships emerge as crucial elements to guarantee the quality of products and services, operational efficiency, competitive deadlines, and fair prices. The barriers are fierce competition, dependence on imported inputs, lack of loyalty, and logistics network deficiencies. The findings showed that involvement and synergy between different stakeholders help develop dynamic capabilities and drive mechanisms to implement resources and relationships critical to creating value and competitive advantage. Additionally, the insights can guide the formulation of actions and strategies to promote the advancement of core technologies in emerging countries’ PV industry.